Analysis of the Benefits of Role-Play in Early Childhood: A Systematic Literature Review - Fatimah, Maya; Widhiasih, Angger Prima (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This systematic literature review (SLR) analyzes the benefits of role-playing activities for early childhood development, focusing on cognitive, social, and emotional domains. The study is grounded in the increasing need for effective and developmentally appropriate learning strategies in early childhood education. Role-playing is selected due to its interactive and imaginative nature, which fosters holistic growth in young learners. The review employs a qualitative method by synthesizing findings from 20 peer-reviewed journal articles published between 2015 and 2024. These studies involved early childhood learners aged 3–6 years in various educational settings, including kindergartens and early childhood centers across Indonesia, the United States, and Finland. The results reveal that role-playing significantly improves children's verbal communication skills (increased by 35% in five studies), cooperative behavior (enhanced by 42% in seven studies), and emotional regulation (reported improvement in 60% of cases). Additionally, several sources report an increase in creativity and problem-solving abilities through role-play scenarios. The findings confirm that role-playing is a valuable pedagogical tool in early childhood education. In conclusion, the review highlights the importance of integrating structured role-play into early learning curricula to support comprehensive child development. Further empirical research is recommended to assess its long-term impact across diverse cultural contexts.